Studying toxic responses of ZnO and TiO2 nanoparticles on fibroblast cells using in vitro testing - Choo, Yeow Chun (2014)
Nanomaterials have been receiving a lot of attention in recent years and are undergoing intense safety screening as their size and nature could elicit toxicity which their micron or other larger counterparts do not exhibit. Most of the literature so far have focussed on how individual nanoparticles induce toxicity in various cell types while little has been reported on multiple nanoparticles’ effect. In some commercial applications such as sunscreens, two nanoparticles, zinc oxide and titanium dioxide, are used together to serve as physical filters against UV radiation. Hence there is a need to model dual nanoparticle toxicity on cells. In this study, we have tested the dual nanoparticle toxicity on Human Dermal Fibroblasts and Human Primary Epidermal Keratinocytes in vitro. The cell types were chosen as sunscreens have a direct contact with the skin. It was found that TiO2 nanoparticles when treated to the cells prior to treatment with ZnO, could recover some of the metabolic activity or protect the cells from the toxicity induced by ZnO. Results have displayed that there is a dependence on duration of treatment, concentration of TiO2 NPs and the surface chemistry of the nanoparticles.